A model for the dynamics of Ross River Virus in the Australian environment. Issue 1 (1st January 2017) - Denholm, Luke; Beeton, Nicholas J.; Forbes, Lawrence K.; Carver, Scott
Abstract: Ross River Disease is a mosquito-borne viral condition that affects pockets of the Australian human population, and can be debilitating in some instances. The evidence is that the virus reservoirs in marsupials, such as kangaroos, and this may account for the unpredictable outbreaks of the disease in humans. Accordingly, we present here a new model for the dynamics of Ross River Virus (RRV) in populations of mosquitoes and kangaroos. We calculate steady-state populations for the sub-groups in each species and demonstrate that naturally-occurring oscillations in the populations (limit cycles) do not occur. When seasonal forcing of vector populations and kangaroo birth rates is taken into account, however, the model may predict multi-annual outbreaks and chaos, perhaps explaining the unpredictability of some RRV disease epidemics, particularly across southern Australia. Detailed results in this case are presented.